Complementary killing activities of Pbunavirus LS1 and Bruynoghevirus LUZ24 phages on planktonic and sessile Pseudomonas aeruginosa PAO1 derivatives - Billaud, Maud; Plantady, Clarisse; Lerouge, Benoît; Ollivier, Emma; Lossouarn, Julien; Moncaut, Elisabeth; Deschamps, Julien; Briandet, Romain; Cleret, Aurore; Fevre, Cindy; Demarre, Gaëlle; Petit, Marie-Agnès (bioRxiv, 2025)
Four P. aeruginosa phages active against a representative panel of strains, and with complementary spectra of action were chosen with the goal of using them for phage therapy. Two of them were myoviruses belonging to the Pbunavirus LS1 species, and two were podoviruses belonging to the Bruynoghevirus LUZ24 species. In order to better apprehend the interactions of these phages with their P. aeruginosa host bacteria, we undertook the characterization of their bacterial receptors, using a PAO1 derivative as a recipient strain. Whereas the receptor of the P. LS1 phage Ab27 had already been characterized as the O-antigen chain of the lipopolysaccharides, no information was available at the onset of this work on the receptor used by the phages of the B. LUZ24 species. We show that the surface polysaccharide Psl is this receptor. Psl stands for polysaccharide synthesis locus, and it is an important component of the biofilm matrix in a large panel of P. aeruginosa strains, including PAO1. Remarkably, the B. LUZ24 phages were more active against PAO1 in minimal medium compared to rich medium. Consistently, this was correlated with larger amounts of Psl bound at the bacterial surface during exponential growth in the minimal medium compared to the rich medium. Biofilms formed on a medical intubation device, as well as in in 96-well plates, were degraded to different extent by the two phage species: biofilms grown for 7 hours on tubing device were degraded more efficiently by the B. LUZ24 than the P. LS1 phage, whereas mature biofilms (16 hours) formed in 96-well plates were degraded more rapidly by P. LS1 than by B. LUZ24 phage. The frequency of genetic mutants resisting to each phage were determined in liquid medium by a fluctuation assay and found in the range of 10-5 to 10-6 per generation. Interestingly, most of the P. LS1 resisting mutants were more sensitive to the B. LUZ24 phage. We conclude that the combination of the four selected phages has very promising properties, which should be relevant in the framework of phage therapy.